Perkembangan Gerakan Pembebasan Hijaz dan Anti Ibn Saud, 1920-an hingga 1930-an: Development of the Hijaz Liberation Movement and Anti Ibn Saud, 1920s to 1930s - Abdullah, Rabiatul Adawiyah; Haris, Abu Hanifah; Abdul Rahman, Zulkanain (Journal of Al-Tamaddun, 2023)
This article discusses the development of the Hijaz liberation and anti-Ibn Saud movements from the 1920s to the 1930s. The emergence of three movements for the liberation of Hijaz and anti-Ibn Saud proves that the movement is very significant and anti-Ibn Saud. Therefore, this article is highlighted to examine the early development of the Hijaz liberation movement and the anti-Ibn Saud, namely the Hijaz National Party (HNP), in addition to evaluating the development of the Hijaz liberation movement and the anti-Ibn Saud movement, namely the Ikhwan movement and the Hijaz Liberation Party (HNP). This study uses qualitative methods and library research by analyzing primary and secondary sources. Among the primary sources used are the Foreign Office (FO), Colonial Office (CO) and Political and Secret Department Record (IOR/L/PS) had obtained from The National Archives and the British Library, London. The results of the study found that the emergence of the anti-Ibn Saud movement in the Hijaz appeared after the conquest of the Hijaz by Ibn Saud who sought to dominate the Hijaz through a political and administrative approach. There were three movements that opposed Ibn Saud at that time, namely the Hijaz National Party, the Ikhwan movement and the Hijaz Liberation Party. Nevertheless, the struggle of all these movements eventually failed and was successfully removed by Ibn Saud starting with the banning of the HNP in 1926, followed by the decline of the Brotherhood movement in the early 1930s. The establishment of the state of Saudi Arabia in 1932 succeeded in challenging the HLP struggle leading to the banning of the movement in 1936.